Instrument validation of website quality to attract donation - Yusuf, Sarina; Ibrahim, Muhamad Shamsul; Megat Ibrahim, Nan Zakiah; Ayub, Suffian Hadi; Salehhuddin Sharipudin, Mohamad Noor; Hassim, Nurzihan (Universiti Sultan Zainal Abidin, Malaysia, 2023)
Background and Purpose: With fund scarcity eminent in Malaysia, soliciting donations effectively is essential to any non-profit organisation (NPO). Many NPOs struggle to raise funds to execute a beneficial project for society. The dimensions to identify relevant online factors influencing the NPO website user decision-making process slowly evolved in a local context due to limited interest in exploring this field. This research was conducted to identify relevant variables related to NPO website user interest to donate. However, a proper instrument must be developed to meet the research aim. Thus, this research was conducted to identify relevant variables and items in the research instrument. Methodology: The study collected 269 responses from ten popular NPO website users. Their responses were recorded using the five-point Likert Scale questionnaire ranging from strongly agree to strongly disagree. At first, the study conducted a content validity test and a pre-test. The sample size is determined based on the SEM requirement. Finally, the responses are analysed using pooled confirmatory factor analysis to determine the instrument reliability and validity. Findings: Only seven variables are retained after the validity and reliability analysis, with 43 items out of 74 items. The result indicated only information, system, service quality, perceived ease of use, and trust are relevant for the NPO to meet website user satisfaction and influence their decision to donate. Contributions: The finding is essential as a guideline to develop a website that meets user preferences. The result also contributed to the website quality literature for the non-profit sector.